Framework to assess the maturity level of learning analytics in higher education and drive learning services improvement - Alenezi, Abdullah (Cranfield University, 2020)
This research was aimed at developing a framework that could be utilised to assess the maturity level of learning analytics (LA) in virtual learning environment (VLE) in higher education institutions (HEI). The assessment of the maturity level of LA in VLE in HEI contributes to enhancing the educational learning programmes and academic services offering to the learners. The successful implementation of LA in an HEI could help improve teaching and learning processes, thereby improving students’ learning experiences (Larrabee Sønderlund et al., 2019; Sclater et al., 2016; Waheed et al., 2020). However, most HEIs often do not know where to start from in implementing programmes for using VLE and LA; thus, the contribution of this study to offer guidance for HEIs. In order to develop the LA maturity assessment framework, a multi-phases methodological approach was adopted which involved 6 key phases (understanding the literature, a field study to gain a high-level perspective of VLE and LA, development of LA maturity model, development of a performance measurement tool, formulation of road map recommendations, and case study validation and expert judgment). The developed LA maturity model comprises of five levels: basic (level 1), developing (level 2), functional (level 3), advanced (level 4) and optimised (level 5). In determining these LA maturity level, the performance measurement tool has to be applied. This performance measurement tool assesses an HEI’s performance in four key components of LA: process, infrastructure, data and human resources and skills. The LA maturity model and performance measurement tool facilitate the road map recommendations. Based on an HEI’s assessed LA maturity level, recommendations are suggested on how progress can be made in LA implementation. The developed LA assessment framework was validated through case studies (PAAET and Cranfield University) and expert judgement that proved its validity and application to different educational contexts. The case study validation showed the differences in performance scores and maturity levels of the two HEIs with specific recommendations relevant to each context being made. Expert judgements highlighted the contribution of the framework to LA which is a relatively new area of research.
Keywords: Learning analytics; virtual learning environment; higher education institution; multi-phases approach; maturity model; performance measurement tool; road map recommendation